Karakteristik Pengamat (Bystander) Cyberbullying Pada Siswa di Sekolah Menengah Kejuruan - Zakiyah, Zakiyah; Hajar, Siti (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2024)
Cyberbullying refers to the unpleasant treatment a child or adolescent receives, such as being insulted, threatened, humiliated, or targeted by peers. This phenomenon is common among adolescents, particularly students, who play a significant role as bystanders, either directly or indirectly. This study aims to understand the characteristics of grade XI students at SMK Negeri 40 East Jakarta in their roles as bystanders in cyberbullying. A descriptive quantitative approach was used, with a sample of 206 students selected through a saturated sampling technique. The measuring instrument was a Likert scale questionnaire with 41 items validated for bystander cyberbullying. Data were collected using the CBS (Cyberbullying Bystander Scale) questionnaire. Results showed that the majority of respondents were female (75.2%) and most were 17 years old (74.8%). Analysis revealed that the highest scoring indicator was Offline Victim Defender, with a maximum score of 43 and an average of 23.20, indicating students were more active in defending victims offline than online. Conversely, the Online Passive Outsider indicator had the lowest score, with a maximum of 19 and an average of 10.18, indicating that students tend to be less passive online.